The Effect of Good Corporate Governance, Third Party Funds and Asset Growth through Profitability on Bankruptcy Risk of Sharia Commercial Banks Listed on the Indonesia Stock Exchange - Lu’lu'il Maknuun; Muhtadina Annisa (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2021)
The aims of this research were to examine the effect of good corporate governance, third party funds and asset growth through profitability to the bankruptcy risk in Islamic Banking which listed in Indonesia stock exchange. The subjects of the research were Islamic Banks which listed in Indonesia stock exchange. Technique in collecting data was purposive sampling method in which it obtained three Islamic Banks. In analyzing the data, the researcher used Partial Least Square (PLS). The results of the research were good corporate governance had significant negative effect on profitability, third party funds had significant positive effect on profitability, and asset growth had significant positive effect on profitability. Then, good corporate governance, third party funds, and asset growth had significant negative toward the bankruptcy risk.